Design and development of a new generation of UV-visible-light-driven nanosized codoped titanium dioxide photocatalysts and biocides/sporocides, and environmental applications - Hamal, Dambar B. (Kansas State University, 2009)
For solar environmental remediation, a new generation of nanosized (< 10 nm) titanium dioxide photocatalysts codoped with metals and nonmetals, or metals only were prepared by the xero-gel and aero-gel methods. For silver or cobalt-based xero-gel titanium dioxide photocatalysts, photoactivities tests revealed that codoping of titanium dioxide with a metal (1% Ag or 2% Co) and nonmetals (carbon and sulfur) is necessary to achieve high-activities for acetaldehyde degradation under visible light (wavelength > 420 nm). It was concluded that high visible-light-activities for acetaldehyde degradation over codoped titanium dioxide were attributed to an interplay of anatase crystallinity, high-surface area, reduced band-gap (< 3.0 eV), uniform dispersion of doped metal ions, and suppressed recombination rate of photogenerated electron-hole pairs. Moreover, the nature and amount of codoped metals play a significant role in visible-light-induced photocatalysis. Metals (Al, Ga, and In) doped/codoped titanium dioxide photocatalysts were prepared by the aero-gel method. The photocatalytic studies showed that activities of metal doped/codoped photocatalysts under UV light (wavelength < 400 nm) were found to be dependent on pollutants. Indium demonstrated beneficial effects in both textural and photocatalytic properties. Gallium and indium codoped titanium dioxide photocatalysts displayed even better performance in the CO oxidation reaction under UV light. Notably, titanium dioxide codoped with Ga, In, and Pt, exhibited unique photoactivities for the CO oxidation under both UV and visible light irradiation, indicating that this system could have promise for the water-gas shift reaction for hydrogen production. Silver-based nanostructured titanium dioxide samples were developed for killing human pathogens (Escherichia coli cells and Bacillus subtilis spores). Biocidal tests revealed that silver, carbon, and sulfur codoped titanium dioxide nanoparticles (< 10 nm) possess very strong antimicrobial actions on both E. coli (logarithmic kill > 8) and B. subtilis spores (logarithmic kill > 5) for 30 minute exposures in dark conditions compared with Degussa P25. It was believed that the carbon and sulfur codoped titanium dioxide support and Ag species acted synergistically during deactivation of both E. coli and B. subtilis spores. Thus, titanium dioxide codoped with silver, carbon, sulfur can serve as a multifunctional generic biocide and a visible- light-active photocatalyst.
Keywords: Nanosized Titanium Dioxide; Visible-light-active photocatalyst; Biocide-Sporocide; Codoped Titania; Photooxidation; Environmental applications; Chemistry, Inorganic (0488); Engineering, Materials Science (0794); Environmental Sciences (0768)